2022
DOI: 10.1039/d2en00451h
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials for enhancing photosynthesis: interaction with plant photosystems and scope of nanobionics in agriculture

Abstract: The complex process of photosynthesis requires precise arrangements of light harvesting molecules in the photosynthetic system. Artificial imitation of such reaction systems is difficult as they involve complex protein structures....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 297 publications
(408 reference statements)
0
6
0
Order By: Relevance
“…The NPs inhibited ATPase activity except for 10 mg L −1 g-TiO 2 NPs (up 14%), which directly down-regulated ATP production in the photochemical phase. Moreover, insufficient NADPH and ATP will prevent the process of carboxylation, reduction, and regeneration in the Calvin cycle, 33 because 3-phosphoglycerate (PGA) and glyceraldehyde-3-phosphate (GAP) as photosynthetic intermediates cannot be converted without catalysis of ATP and NADPH. Carboxylation is the first step for CO 2 to enter the plant, and this process is regulated by Rubisco, which catalyzes CO 2 into energy-rich metabolites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPs inhibited ATPase activity except for 10 mg L −1 g-TiO 2 NPs (up 14%), which directly down-regulated ATP production in the photochemical phase. Moreover, insufficient NADPH and ATP will prevent the process of carboxylation, reduction, and regeneration in the Calvin cycle, 33 because 3-phosphoglycerate (PGA) and glyceraldehyde-3-phosphate (GAP) as photosynthetic intermediates cannot be converted without catalysis of ATP and NADPH. Carboxylation is the first step for CO 2 to enter the plant, and this process is regulated by Rubisco, which catalyzes CO 2 into energy-rich metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…2C) because the electron transport from Q A to Q B requires Fe catalysis, 32 and the electron transfer from the cytochrome b 6 f complex to photosystem I (PSI) is associated with Cu. 33 More information on the correlation between TiO 2 NPs and electron transfer will be further explored below. In addition, insufficient levels of Mn, an important metal cofactor for electron transfer in PSII, were also associated with decreased ΦPSII and ETR.…”
Section: Response Of Photosynthetic Parametersmentioning
confidence: 99%
“… Potential risk of NMs in agricultural application. NMs in the environment are capable of forming compounds with complex environmental contaminants . There is still a lack of studies on their effects on plants.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…NMs in the environment are capable of forming compounds with complex environmental contaminants. 175 There is still a lack of studies on their effects on However, the phytotoxicity induced by NMs has been widely reported. 176,177 NMs can impede crop growth, including roots and stems.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…64 Furthermore, nanomaterials consisting of essential minerals/metals have been used for inducing plant growth and crop production. 65,66 In one of the most recent studies, Yue et al (2022) have shown that the foliar application of manganese ferrite (MnFe 2 O 4 ) nanomaterials on tomato plants significantly improves the early flowering and production of tomatoes. 67 The authors have also demonstrated that the potential effects of nanomaterials occurred because of an increase in chlorophyll content and ferredoxin, PsaA, and PsbA upregulation in leaves, which eventually triggered the photosynthesis efficiency of plants.…”
Section: Presence Of Fe-cnf On Mof Enhanced Translocation and Bioavai...mentioning
confidence: 99%